2008
DOI: 10.2174/1874098700802010069
|View full text |Cite
|
Sign up to set email alerts
|

A Mossbauer Study of the Low Spin-High Spin Transition of an Oxygen Adduct Formed in Solid β -Fe(II)Phthalocyanine

Abstract: Several oxygen adducts are formed when oxygen is diffused into the interplanar spacings of solid -Fe II Pc suspended in water. The constraints imposed by the solid matrix induce formation of interesting oxygen adducts which cannot be synthesized by regular solution chemistry. One of the oxygen adducts exhibits low-spin to high-spin transition with considerable thermal hysteresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Since the oxygenation of the FePc complex is the key step in the synthesis, there is a great interest in the exploration of the interaction of oxygen with FePc. In our previous studies, temperature-dependent Mössbauer spectra showed interconversion of low-spin species into high-spin species upon raising the temperature [3][4][5]. Based on the XRD and Mössbauer spectroscopic data, the formation of long -peroxo bridged -Fe-O-O-Fe-chains are suggested upon the introduction of high amount of oxygen into the lattice of -FePc [6].…”
Section: Introductionmentioning
confidence: 89%
“…Since the oxygenation of the FePc complex is the key step in the synthesis, there is a great interest in the exploration of the interaction of oxygen with FePc. In our previous studies, temperature-dependent Mössbauer spectra showed interconversion of low-spin species into high-spin species upon raising the temperature [3][4][5]. Based on the XRD and Mössbauer spectroscopic data, the formation of long -peroxo bridged -Fe-O-O-Fe-chains are suggested upon the introduction of high amount of oxygen into the lattice of -FePc [6].…”
Section: Introductionmentioning
confidence: 89%
“…In our next study of the oxygenated β-iron(II) phthalocyanine, we observed the formation of an oxidized Fe III species, and we also found the temperature-dependent spin transition (SCO) for one of the Fe III components [ 40 , 41 ]. This process is illustrated in a series of overlaid spectra shown in Figure 11 .…”
Section: Temperature-dependent Spin Transitions and Antiferromagnementioning
confidence: 99%